"Polymer-in-ceramic" PEO/2D heterojunction composite electrolytes for solid-state batteries. Issue 1 (1st December 2022) - Dong, Xingfang
Abstract: The ferroelectric spontaneous polarizability of the piezoelectric TBA + CNO − also has an enhanced effect on ion transport and electrode interface modification, and its ferroelectric spontaneous polarization field also helps to reduce the generation and growth of anode dendrites. The structural instability of LRAP electrolyte Li2.99 Ba0.005 OCl are maintained by forming a heterojunction structure with two-dimensional nanosheets TBA + CNO −, and the fast conduction channels of lithium ions (Li + ) are established. Composite electrolytes possess Li + conductivity σi > 10 −4 S/cm at 25°C. The composite materials composed of "polymer-in-ceramic" with flexibility and mechanical strength are fabricated by the casting method. PEO-Li2.99 Ba0.005 OCl/TBA + CNO − shows good compatibility with lithium metal, forming a stable solid electrolyte interface. The plastic crystal electrolyte dripped on the cathode side avoids the direct contact between high-voltage cathode and electrolyte and protects PEO from being oxidized and decomposed. NCM811 |Li batteries show 70.9 mAhg −1 with capacity retention of 97.88% after 100 cycles.